Quickly Understanding of Hypertension Incident in Rural Populations: A Cross-Sectional Study - Niluh Desy Purnamasari; I Wayan Supetran; Desak Eka Susianawati (Jurnal Kesehatan Masyarakat, 2026)
Abstract: This study aims to identify the main determinants of hypertension in rural areas by looking at the influence of diet, age, gender, and employment status in the community of Tagolu Village, Lage Sub district, Poso District. Hypertension, known as the “silent killer”, is one of the leading causes of death globally, with more than 1.13 billion sufferers. This is a quantitative study with a cross-sectional design in 2022. 57 respondents from 134 populations were randomly drawn. The research instrument used a validated questionnaire. Data analysis was performed using the Chi-square test with a significance level of 95% using SPSS. The main results of the study indicate a significant association between dietary patterns and the incidence of hypertension (p = 0.001; OR = 50,000; 95% CI: 9,175–272,466), with poor dietary patterns having a prevalence of hyperten-sion of. Although the variables of age (OR = 1.579), gender (OR = 1.429), and employment status (OR = 0.700) did not show statistical significance (p > 0.05), the OR values indicate a trend toward increased risk of hypertension in the elderly and male groups, while employment status did not have a significant effect. Research findings indicate that poor dietary patterns are strongly associated with hypertension. .